Molecular Method for Bartonella Species Identification in Clinical and Environmental Samples - García-Esteban, Coral (American Society for Microbiology (ASM), 2008)
A new, efficient molecular method for detection of Bartonella, based on the 16S-23S rRNA intergenic spacer and 16S rRNA amplification by multiplex PCR combined with reverse line blotting, was designed. This assay could simultaneously detect 20 different known species and other Bartonella species not described previously.